FUNDAMENTAL CONCEPTS OF METALANGUAGE OF SINGULAR DESCRIPTION OF IDIOM AS A REAL LANGUAGE SYSTEM - Hromko, Tetiana (Linguistic Bulletin (Movoznavchyi Visnyk), 2023)
Introduction. The problem of the study is to understand and analyze the use of the concept of “meta-language” in linguistics as a means of describing other natural languages and idioms; to clarify its significance in the scientific study of language systems, to develop a system of meta-language units for the real description of different idioms, taking into account the specifics of the linguistic system, methods and tools for linguistic description and analysis of linguistic phenomena. The purpose of the study is to analyze the concept of meta-language in the monolingual description of the idiom as a real language system, which is a new aspect of research and is becoming more relevant in dialectology due to the unification of terminology in linguistic terms. Results. The meta-description language is used in applied linguistics with its positioning as a tool for descriptive analysis not only of natural languages, but also of individual idioms. In idiomology as a science of idiom, linguistic data constitute a certain mono-linguistic linguarium, which distinguishes the metalanguage of its description from dialectological or other types of linguistic terminology, and thus positions the specifics of descriptive analysis of a dialect as a real language system in the context of highly organized conceptual approaches to the language system. The article outlines the problems of meta-language monolingual description, which are in the lens of modern theoretical and methodological linguistic paradigms, since the language of linguistics is also considered a meta-language, which is characterized by a complete set and classification of linguistic knowledge. It is noted that the use of a meta-language in the study of a idom contributes to the unification of the description of the system of linguistic concepts and the descriptions of the linguistic vocabulary, and therefore the fundamental concepts are the object and expression of another language. A monoidiom description of a language based on a complete set of linguistic data, rather than on differentially distinguished dialectal materials, has specifics of the meta-language apparatus and methodological principles, which requires updating the system of basic principles and special methods of linguistic research, as well as presenting methodological nominations and research apparatus necessary for analyzing the real language system of the idiom. Originality. The scientific novelty of the study of the meta-language of linguistic descriptive analysis is to recognize it as a special tool for linguistic analysis of the idiom discourse and composition, which includes both general linguistic terms and concepts (idiom, idiom speaker) and supplemented and distinct methodological concepts of monoidiom linguistic description: idiom community, idiom communication, idiom language. Its specificity lies in the use of linguistic theory for a more accurate and reliable assessment of the speech and language repertoire of the idiom. Conclusion. The use of a meta-language to describe an idiom as a real language system is proposed. A monoidiom description of a language has specifics of the meta-language apparatus and methodological principles that require updating the system of basic principles and special methods of linguistic research. Such a language description is based on a complete set of linguistic data, not on differentially distinguished dialectal materials. The use of a meta-language in the study of the idiom contributes to the unification of the description of the system of linguistic concepts and the descriptions of the lingual of the idiom. A full presentation of the metalanguage of monoidiom description of the lingual is given in the glossary of meta-language description for the idiom language system.